Relasi Antar Aktor Dalam Upaya Pemenuhan Kebijakan Energi Baru Terbarukan Di Provinsi Bali Tahun 2019 - Wiswadhipa, Anak Agung Gde Prana; Azhar, MuhammadxAli; Putri Wirantari, I Dewa Ayu (Jurnal Nawala Politika, 2020)
ABSTRACT This x study x aims to x find out how the policy x making process that involves many parties to carry out a collaborative mechanism that forms relationships between politics actors in the effort to fulfill the renewable energy policy in x Bali onx 2019 th . This study using the Policy Windows theory by John Kingdon as a formulation of the policy agenda of the problems in this study. The x research method x used in this research is a x descriptive qualitative , which is more concerned about the characteristics, x quality, x nterrelationships of activities in relation to politicsx actors and relations in the fulfillment of x 2019 renewable energy policies. Results of This research is: energy problems in the Province of Bali, which if the agenda setting through cooperation (acto rx relations) to give birth to several MoUs that become the reference for the Government of x Bali Province in formulating policies in the form Governor x Regulation n o. 45 about clean x energy and encourage the legislature to immediately x draft a bout clean energy x policy . Keywords : ActorxRelations,Renewable Energy, Policy Windows